XYZ COFFEE IN THE DIGITAL ERA : ANALYSIS OF BRAND TRUST AND CUSTOMER ENGAGEMENT AS DETERMINANTS OF PURCHASE DECISION - Devanof, Haferta; Kurniawati, Kurniawati (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study analyzes the role of social media marketing activities in influencing purchase intention and purchase decision for XYZ Coffee, with brand trust, brand attitude, and customer engagement acting as mediating variables. A quantitative explanatory approach was employed, involving 200 active social media users in Indonesia who had previously purchased products from XYZ Coffee. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results demonstrate that social media marketing activities exert a significant direct effect on purchase decision and an indirect effect through brand trust, brand attitude, and customer engagement. Among the mediating variables, brand attitude and customer engagement play a dominant role in strengthening purchase intention, which subsequently leads to purchase decision. These findings indicate that the success of digital marketing strategies depends not only on social media visibility but also on the company’s ability to build positive brand perceptions, foster trust, and create meaningful interactions with consumers. This study contributes to the advancement of digital marketing and consumer behavior literature by proposing an integrated framework applicable to coffee brands and fast-moving consumer goods competing in highly dynamic digital environments. Keywords : Brand Attitude; Brand Trust; Customer Engagement; Purchase Intention; Purchase Decision